2018
DOI: 10.1016/j.ejmech.2018.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Modified carbazoles destabilize microtubules and kill glioblastoma multiform cells

Abstract: Small molecules that target microtubules (MTs) represent promising therapeutics to treat certain types of cancer, including glioblastoma multiform (GBM). We synthesized modified carbazoles and evaluated their antitumor activity in GBM cells in culture. Modified carbazoles with an ethyl moiety linked to the nitrogen of the carbazole and a carbonyl moiety linked to distinct biaromatic rings exhibited remarkably different killing activities in human GBM cell lines and patient-derived GBM cells, with IC 50 values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“… 12 In previous studies, we developed MDAs (ST-34, ST-360, and ST-377) that bind to the colchicine site of tubulin, inhibit MT assembly, and kill glioma cells in culture (ie, compounds 8, 20, and 27 in ref. 13 ; Figure 1A ). Here we leveraged these results as the starting point to develop a novel chemical entity, ST-401, and studied its MOA and antitumor activity in glioma cells in culture and in the RCAS/tv-a PDGFB-driven glioma mouse model.…”
mentioning
confidence: 99%
“… 12 In previous studies, we developed MDAs (ST-34, ST-360, and ST-377) that bind to the colchicine site of tubulin, inhibit MT assembly, and kill glioma cells in culture (ie, compounds 8, 20, and 27 in ref. 13 ; Figure 1A ). Here we leveraged these results as the starting point to develop a novel chemical entity, ST-401, and studied its MOA and antitumor activity in glioma cells in culture and in the RCAS/tv-a PDGFB-driven glioma mouse model.…”
mentioning
confidence: 99%
“…Recently, a series of carbazole-based MT targeting agents with anti-tumor properties has been reported, confirming the ability of this type of chemical scaffold to interact with the colchicine site of tubulin [28]. The Carba1 scaffold is a versatile one and we are currently synthesizing modified analogs for medicinal chemistry optimization.…”
Section: Discussionmentioning
confidence: 95%
“…Unlike Carba1, they exert potent killing activities in human glioblastoma cells. A possible explanation for the difference in cytotoxicity observed between Carba1 and the compounds described by Diaz et al [ 24 ] may reside in a lower affinity of Carba1 for the colchicine binding site of the tubulin dimer. Indeed, we found that the affinity of Carba1 for the colchicine site is not very high, in the micromolar range.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, a series of carbazole-based MT targeting agents has been reported [ 24 ]. These acyl-substituted derivatives, conceived as analogs of nocodazole, represent other examples of carbazole scaffolds able to interact with the colchicine site of tubulin.…”
Section: Discussionmentioning
confidence: 99%